Empirical Verification of S. Schwartz's Theory of Basic Human Values Among Polish Managers - Brzozowski , Maciej; Bartkowiak , Paweł (Studia Oeconomica Posnaniensia, 2014)
In the first part of the paper the principal elements of S. Schwartz's concept of basic human values are delineated. In the second part of the paper the findings of empirical research conducted among managers from Polish companies are described. The findings presented reflect three research areas: (1) the importance of mangers' personal values, (2) the structure of managers' personal values, (3) a comparison of the importance of managers' personal values according to gender, position, work experience, age and level of education, as well as the size of the organization.